Försök med olika såmaskiner vid konventionell sådd och direktsådd - Magnusson Kroon, Gustaf (SLU/Dept. of Soil and Environment, 2015)
In this thesis, two studies with different drills were included. In one of the studies two drills were compared: Väderstad Rapid and Väderstad Spirit. In the other study various drills for direct drilling were compared. The study with Rapid and Spirit was placed in two locations with different autumn tillage; one on ploughed land in Uppsala and one on cultivated land in Västerås, both with relatively high clay content. Rapid drills have a single disc coulter, while the Spirit drills have a double disc coulter. Various aspects were compared such as aggregate distribution, seed placement, emergence, crop yield and economic outcome. At both locations, a higher proportion of small aggregates was observed at higher tillage intensity (harrowing frequency). In the ploughed experiment few differences were observed in seed placement, but in the autumn cultivated experiment it was observed that the Spirit drill had placed a greater percentage of seeds in loose soil. At both sites drilling with Rapid gave higher emergence than drilling with Spirit. There was no significant correlation between seed placement and emergence although there was a trend towards that an increased proportion of seeds in the seedbed bottom gave a higher emergence. In the ploughed experiment harrowing three times before Rapid drilling gave the highest yield and highest net economic outcome, while Spirit drilling without harrowing and after one harrowing gave the lowest yield and lowest economic outcome. In the cultivated experiment direct drilling with Rapid without harrowing gave the highest yield and the highest economic outcome while the other treatments were relatively similar in yield; about 15-20 percent below the Rapid direct drilling. Hence increased tillage intensity decreased the economic outcome. In the second study four different drills were compared for direct drilling, one was also used in autumn cultivated soil as a reference. The machines tested were Väderstad Rapid in cultivated soil and for direct drilling, Väderstad SeedHawk with tines and disc coulters and VM SK 300, which is a disc coulter machine. Also in this study aggregate distribution, seed placement, emergence, yield and economics were determined. In this trial no differences in aggregate distribution were observed but the greatest volume of loose soil was observed in the autumn cultivated plots. This was also where the lowest percentage of peas in loose soil was found, followed by the SeedHawk with tines treatment. Highest emergence was found in the autumn tillage plots followed by the two SeedHawk treatments. The highest yield was observed for Rapid after autumn tillage, which also resulted in the highest economic outcome. The differences between the other drills were small. It can be determined that the cost for the additional processing was compensated with a higher yield compared to pure direct drilling.